Elevating South Africa's entrepreneurial activity in the fourth industrial revolution era - Patrick Ssekitoleko; Shepherd Dhliwayo (Administrative Sciences, 2023)
The objective of this research is to appraise the level of entrepreneurial activity in South Africa and to identify the challenges to implementation of the fourth industrial revolution (4IR) that obstruct the leveraging of 4IR technologies to boost entrepreneurial activity in the country. A conceptual exploratory literature review approach was applied. This study's results show that a high unemployment rate, the quality of entrepreneurial support initiatives, physical infrastructure, enterprise funds and increased economic freedom are enablers of entrepreneurial activity in South Africa. High data costs, poor digital technological preparedness, an unreliable energy supply, data protection and cyber security risks, among other factors, were identified as obstacles to 4IR implementation. We, therefore, recommend a 4IR fund, mandatory data price laws, proactive policing, further public-private partnerships, enhancement of whistle-blower protection laws, among others, as solutions to buoy entrepreneurial activity through application of 4IR technologies. These results signal the need to ensure a synchronized effort by all relevant spheres of government to address the 4IR implementation challenges and enhance entrepreneurial activity for South Africa's economy.
Keywords: 350; entrepreneurial activity; determinants; entrepreneurship; fourth industrial revolution (4IR); 4IR implementation challenges; South Africa